Analisis tingkat pengetahuan mahasiswa program studi pendidikan dokter tahun ajaran 2017-2018 Universitas Udayana tentang prescribing error - Nabila Putri Rachmawati; Desak Ketut Ernawati; I Gusti Ayu Artini (Intisari Sains Medis, 2019)
Introduction: Prescribing Errors is a failure in the treatment process leading to or potentially harmful to the patient, this error most often occurs although it can be prevented. The incidence of prescribing errors continues to increase from year to year, but data in Indonesia that discusses the level of knowledge of medical students about prescribing errors is still small. The purpose of this study is to determine the level of knowledge of medical student study program 2017-2018 academic year at Udayana University Denpasar about prescribing errors.Method: This research is a descriptive cross sectional study conducted at the Medical Faculty Udayana University Sudirman Campus Denpasar. Data obtained in the form of primary data questionnaire. Data were analyzed using software computer.Result: The results showed that the most gender are women of 68 students (66%). The largest proportion of age is 19-20 years old number of 52 students (52%). Groups of semesters 1, 3, 5 and 7 obatined a similar proportion of 25 students (25%). The level of students' knowledge of prescribing case study is classified into moderate category with mean 3,7-7,1 of 67 students (67%). The number of correct answers in identifying type of error from 3 prescriptions is in the case of the first prescription, the 3rd semester student who is able to identify the prescribing error, with the type of mistake that is wrong dose as many as 14 students (35,9%) with p value = 0,066 and wrong dosage form as 21 students (39,6%) with p value = 0.000. In the case of the second prescriptions, 7th semester students were able to identify the prescribing error, with the type of mistake that is wrong dose as many as 13 students (41,9%) with p value = 0,005 and wrong dosage form as 22 students (36,7%) with p value = 0.000. In the case of the third prescriptions, the 3rd semester students were able to identify the prescribing error, with the type of mistake that is the wrong indication of the drug as many as 15 students (62,5%) p value = 0.000.Conclusion: In this research, it can be concluded that the knowledge level of the majority students is in moderate levelabout 67 (67%). While the remaining respondents good knowledge level as much as 7 (7%) and bad knowledge is as much as 26 (26%).